Metastasis of Pregnancy-Associated Breast Cancer (Suspected to Be Hereditary Breast and Ovarian Cancer) to the Brain, Diagnosed at 18 Weeks’ Gestation: A Case Report and Review of the Literature - Tomohiro Okuda; Sakura Yamamoto; Seiki Matsuo; Hisashi Kataoka; Jo Kitawaki (Case Reports in Obstetrics and Gynecology)
We report a case of pregnancy-associated breast cancer with metastasis to the brain, likely resulting from hereditary breast and ovarian cancer (HBOC). A 35-year-old woman (gravida 2, para 0-1-0-1) underwent a right mastectomy and right axillary dissection after a cesarean section at 30 years of age; her mother died at 47 years of age due to breast cancer. Histopathological examination indicated an invasive ductal carcinoma with triple-negative cancer (cancer stage 2B [pT3N0M0]). The patient refused adjuvant therapy because of the risk of infertility. After 4 years, she became pregnant naturally. At 18 weeks’ gestation, she experienced aphasia and dyslexia due to brain metastasis. The pregnancy was terminated at 21 weeks’ gestation after thorough counseling. Her family history, young-onset disease, and histopathological findings suggested HBOC. She declined genetic testing for BRCA1/2, though genetic counseling was provided. In cases of pregnancy-related breast cancer, consideration must be given to whether the pregnancy should be continued and to posttreatment fertility. HBOC should also be considered. Genetic counseling should be provided and the patient should be checked for the BRCA mutation, as it is meaningful for the future of any potential children. Genetic counseling should be provided even if the cancer is advanced or recurrent.